2015
DOI: 10.1002/jcp.24885
|View full text |Cite
|
Sign up to set email alerts
|

FADD phosphorylation impaired islet morphology and function

Abstract: Previous studies have indicated that Fas-FasL pathway and its downstream caspase-8 can regulate islet mass and insulin secretion. As a classical adaptor in Fas-FasL signaling, Fas-associated death domain-containing protein (FADD) takes part in many non-apoptosis processes regulated by its phosphorylation. However, its role in islets has not been evaluated to date. Here, through comparative proteomics and bioinformatic analysis on FADD phosphorylated (FADD-D) and wild-type (WT) MEFs, we found three proteins inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Several phosphorylation sites have been identified in FADD [89,90,91], but the most relevant site conserved between mice and humans is serine 191 and serine 194, respectively [90]. The impact of FADD phosphorylation on apoptosis is controversial [5,90,92,93]. Our data indicate that the phosphorylation status of FADD does not affect apoptosis [13], but FADD phosphorylation could affect apoptosis indirectly, as a consequence of protein availability in the cell.…”
Section: Posttranslational Modifications Of Fadd Proteinmentioning
confidence: 99%
“…Several phosphorylation sites have been identified in FADD [89,90,91], but the most relevant site conserved between mice and humans is serine 191 and serine 194, respectively [90]. The impact of FADD phosphorylation on apoptosis is controversial [5,90,92,93]. Our data indicate that the phosphorylation status of FADD does not affect apoptosis [13], but FADD phosphorylation could affect apoptosis indirectly, as a consequence of protein availability in the cell.…”
Section: Posttranslational Modifications Of Fadd Proteinmentioning
confidence: 99%
“…In the mouse model of FADD-D (S191D), which mimics the constitutive expression of phosphorylated FADD in mice, the area of pancreatic islets is shrunken, and GSIS is impaired. This suggests that FADD phosphorylation negatively regulates islet development and insulin secretion (Yao et al, 2015).…”
Section: Phosphorylationmentioning
confidence: 98%
“…Fas-associated death domain-containing protein (FADD) is known to regulate insulin secretion and islet development [ 87 ]. FADD phosphorylation has been suggested to be involved in insulin degradation, as evidenced by the compromised insulin production and increased insulin levels in serum of FADD-D (FADD phosphorylation-mimic mutation) mice [ 87 ]. A recent study demonstrated that FADD phosphorylation downregulates the mRNA and protein levels of insulin-degrading enzymes (IDEs) [ 52 ].…”
Section: Ptms In Type 2 Diabetesmentioning
confidence: 99%